2016
DOI: 10.1111/ecoj.12276
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of (Subnational) Fortune

Abstract: Using newly collected subnational data, this article establishes the within-country persistence of economic activity in the New World over the last half millennium, a period including the trauma of European colonisation, the drastic reduction of native populations and the imposition of potentially growth inhibiting institutions. High pre-colonial density areas tend to be denser today due to locational fundamentals and agglomeration effects: colonialists established settlements near existing native populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 85 publications
(208 reference statements)
3
28
0
Order By: Relevance
“…In contrast, Oto-Peralías and Romero-Ávila (2016) find for Spain that the speed of the medieval conquest of the previously Islamic principalities had an impact via land and power inequality on subsequent development (see also Beltrán Tapia and Martínez-Galarraga 2015). The emphasis of all these authors on the subnational level is also based on the finding by several scholars that the regional differences were surprisingly persistent across history (see, for example, on Latin America: Maloney and Valencia Caicedo 2015). Ashraf et al (2017) expanded the human capital determinants to include capital-skill complementarities, also controlling for land inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Oto-Peralías and Romero-Ávila (2016) find for Spain that the speed of the medieval conquest of the previously Islamic principalities had an impact via land and power inequality on subsequent development (see also Beltrán Tapia and Martínez-Galarraga 2015). The emphasis of all these authors on the subnational level is also based on the finding by several scholars that the regional differences were surprisingly persistent across history (see, for example, on Latin America: Maloney and Valencia Caicedo 2015). Ashraf et al (2017) expanded the human capital determinants to include capital-skill complementarities, also controlling for land inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…cities). Studies have shown that geography has a strong influence on spatial development, in both rich and poor countries (Gallup et al ., ; Beeson et al ., ; Rappaport and Sachs, ; Maloney and Caicedo, ; Bosker and Buringh, forthcoming). One implication of geography as a driver for development is that localised historical shocks should only have temporary effects.…”
mentioning
confidence: 99%
“…Not everyone accepts the validity of this hypothesis. More recently, Maloney and Caicedo (2016) have used sub-national pre-colonial population densities for eighteen countries in the Western hemisphere to show that population density has persisted up to today: those countries with highest concentrations in 1500 remain most densely populated. Importantly, those countries also have higher average income levels today, challenging Acemoglu et als hypothesis and suggesting wealth persistence instead.…”
Section: Introductionmentioning
confidence: 99%